Hughes Stovin: Sustained remission and regression of pulmonary aneurysms with anti–tumor necrosis factor treatment. Issue 6 (2nd April 2019) - Ghirardo, Sergio; Pastore, Serena; Gortani, Giulia; Tommasini, Alberto; Taddio, Andrea
Abstract: We report the first case of Hughes Stovin Syndrome successfully treated with long‐lasting tumor necrosis factor α (TNF‐α) blocker (infliximab) treatment. Because of the failure of the standard therapeutic regimen with steroids and cyclophosphamide, infliximab was started achieving a stable disease remission and a complete resolution of pulmonary aneurysms. Hughes Stovin Syndrome, although rare, is a life‐threatening condition that needs to be timely identified and treated aggressively. Our report underlines the importance of TNF‐α blocker treatment in Hughes Stovin Syndrome, suggesting its use as long‐term safe and useful.